The Economy of Central and Eastern Europe during the Global Economic Crisis - Ignasiak-Szulc, Aranka; Kosiedowski, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article discusses the course and results of the process of economic development of Central and Eastern Europe (CEE) in the context of integration with the European Union, with a particular emphasis on conditions connected with the global financial crisis. In the study the CEE economy was characterised against the background of the world and Europe, followed by a presentation and interpretation of the changes in dynamics of economic growth. It was found that these changes were strongly correlated. The text also presents the evolution of the situation on the labour market during the crisis. The article ends with synthetic conclusions from the analyses. The research proves that the process of economic convergence occurred in all CEE countries, which was a positive effect of EU cohesion policy. This process was, however, very diverse, and the global crisis brought about far-reaching, uneven changes, including even a few cases of divergence.